75 Identifying High Priority Conditions for Research in Hospitalized Children Using a Data-driven Approach: A Population-based Study. (21st October 2022) - Gill, Peter; Thavam, Thaksha; Anwar, Mohammed Rashidul; Zhu, Jingqin; Parkin, Patricia; Cohen, Eyal; To, Teresa; Mahant, Sanjay
Abstract: Background: Identifying conditions that should be prioritized for research based on their healthcare system burden is imperative to build a meaningful research agenda for the care of hospitalized children. No previous Canadian prioritization studies have been conducted in this area. Objectives: To determine the prevalence, cost, and variation in cost of pediatric hospitalizations at all hospital types, to identify conditions that should be prioritized for future research. Design/Methods: Population-based cross-sectional study of children (< 18 years), with an inpatient hospital encounter between April 1, 2014 and March 31, 2019 in Ontario, Canada. Data were obtained from linked health administrative databases. For each encounter, the most responsible ICD-10-CA discharge diagnosis code was classified into clinical categories using the Pediatric Clinical Classification System. The condition-specific prevalence and cost of pediatric hospitalizations, and condition-specific variation in cost per encounter across hospitals were determined. The variation in cost was evaluated using number of outlier hospitals, and intraclass correlation coefficient (ICC). Results: There were 627, 314 inpatient hospital encounters from 165 hospitals costing $4.3 billion. A total of 408, 003 (65.0%) hospitalizations and $1.9 billion (43.8%) in hospital costs occurred at general hospitals. Table 1 presents the 25 most prevalent and 25 most costly conditions (34 in total) ranked by cumulative cost. The top 10 costly conditions accounted for 70.0% of all costs and 59.6% of all encounters. Conditions that were highly prevalent and costly included: low birth weight, preterm newborn, major depressive disorder, pneumonia, other perinatal conditions, bronchiolitis, and neonatal hyperbilirubinemia. Figure 1 illustrates the 25 most costly medical conditions, of which the majority of the most prevalent and costly conditions were newborn conditions. Amongst the most costly conditions, the highest variations in cost across hospitals were observed in two mental health conditions (other mental health disorders [ICC = 0.28]; anxiety disorders [ICC = 0.19]), and three newborn conditions (intrauterine hypoxia and birth asphyxia [ICC = 0.27]; other perinatal conditions [ICC = 0.17]; surfactant deficiency disorder [ICC = 0.17]). Conclusion: This study identified several newborn and mental health conditions as the most prevalent, costly, and with high variation in cost across hospitals in hospitalized children. These results can be used to generate a research agenda for the care of hospitalized children in general and children's hospitals to build a stronger evidence-base and improve patient outcomes.